Development of novel ultrasound techniques for imaging and elastography. From simulation to real-time implementation - Ramalli, Alessandro (Premio Tesi di Dottorato, 2013)
Ultrasound techniques offer many advantages, in terms of ease of realization and patients' safety. The availability of suitable hardware and software tools is condicio sine qua non for new methods testing. This PhD project addresses medical ultrasound signal processing and seeks to achieve two scientific goals: the first is to contribute to the development of an ultrasound research platform, while the second is introducing and validating, through this platform, non-standard methods. During the thesis, the capabilities of the system were improved by creating advanced software tools, such as acoustic field simulators, and by developing echo-signals elaboration programs. In particular, a novel technique for quasi-static elastography was developed, in-vitro tested and implemented in real-time.